Perbandingan Algoritma RC4+ dan RC4a dalam Pengamanan File Teks - Lisa Oktasari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Along with the development of technology, documents that are supposed to be confidential can be accessed by unauthorized people. So safeguards are needed to prevent information from reaching unauthorized hands. The security of a text becomes reduced or insecure in terms of storage. It does not cover the possibility of a third party changing or taking the text, then the text is encoded into codes that are not understood, so that if there is a third party who wants to change it will have difficulty translating the actual content of the text and must decrypt it first. The security of encrypting text files, to avoid this problem, it is necessary to carry out a process of hiding or disguising information in such a way that it does not fall to other unauthorized parties. In this study, comparing the RC4 + Algorithm and the RC4A Algorithm in securing text files. Text file security application to help solve security problems of data created or stored using files that are formatted such as doc, txt